Meningkatkan Hasil Belajar dalam Bernalar Kritis Materi Sakramen Baptis dengan Model PBL Fase B Kelas 3 SDN 076075 Meafu, Nias Utara - Duhufati Gea; Nerita Setiyaningtiyas (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2025)
This study aims to improve learning outcomes in critical reasoning on the material of the Sacrament of Baptism through the application of the Problem-Based Learning (PBL) Phase B model in class 3 of SDN 076075 Meafu, Lahewa Timur District, North Nias Regency. The background of the study is the low critical reasoning ability of students in understanding the concept of the Sacrament of Baptism, which has an impact on learning outcomes that have not met the KKM. This Classroom Action Research (CAR) was carried out in two cycles, each consisting of planning, implementation, observation, and reflection. Data collection techniques include cognitive tests, observation of student activities, and documentation. The results of the study showed a significant increase in critical reasoning abilities and student learning outcomes. In the first cycle, students were in the "adequate" and "proficient" categories, but in the second cycle, a significant increase occurred with 2 students reaching the "proficient" category. Recommendations are given to teachers to implement PBL in learning to optimize students' critical thinking skills.